The Relationship of Leverage, Asset Management, Earnings Management and Profitability - Indrayati, Indrayati; Sumiadji, Sumiadji; Jaswadi, Jaswadi; Utami, Rachma (Global Financial Accounting Journal, 2024)
The Aneka Industry sector in 2019 recorded the worst performance. This research aimed to examine the effect of leverage on profitability and the roles of asset management and earnings management as a mediating effect at Aneka Industry Companies in Indonesia. The population of this research was 665 companies listed on the Indonesian Stock Exchange (IDX), and the sample used was 225 for the 2016-2020 period. Data were analyzed using Structural Equation Modelling (SEM)-PLS. The results showed that leverage had a significant negative effect on asset and earning management and a non-significant effect on Profitability. Both asset management and earnings management had a significant positive impact on Profitability. Meanwhile, asset and earnings management successfully mediated the effect of leverage on Profitability. Not many studies have examined the relationship between leverage, asset management, earnings management, and profitability. This research also tested a large sample size to represent conditions in Indonesia. This study recommends that the company maintain the condition of asset management and reduce earnings management.